PENERAPAN MICROSOFT EXCEL SEBAGAI ALAT PENCATATAN KEUANGAN KELAS UNTUK MENINGKATKAN TRANSPARANSI DAN AKUNTABILITAS - Luh Gede Bevi Libraeni; Ni Made Mila Rosa Desmayani; Ni Kadek Liryana Purnama (ASOSIASI IDEBAHASA KEPRI, 2026)
This community service program aimed to address the need for Microsoft Excel proficiency among students at SMP Negeri 14 Denpasar, where limited computer facilities and inadequate training had hindered their ability to effectively use spreadsheet applications. The program was implemented in five stages: initial planning, partner needs assessment, execution, evaluation, and reporting. A preliminary analysis identified two key challenges: insufficient computer infrastructure and low student competency in Excel, particularly for data processing and financial reporting. To bridge this gap, the program provided hands-on training that covered fundamental Excel functions, financial recording techniques, and data analysis, delivered through interactive sessions and practical exercises. Post-training quizzes assessed comprehension, with rewards to motivate participation. Results showed significant improvements in students' Excel skills and their ability to manage classroom finances transparently. This success highlights the importance of targeted, practice-based digital literacy programs in under-resourced educational settings, aligning with national goals of fostering technologically competent graduates. Future expansions of this model could adapt it to broader contexts, ensuring sustainable impact.